Food safety knowledge and practices of abattoir and butchery shops and the microbial profile of meat in Mekelle City, Ethiopia - Haileselassie, Mekonnen (Asian Pacific Tropical Medicine Press, 2013)
OBJECTIVE: To assess the food safety knowledge and practices in meat handling, and to determine microbial load and pathogenic organisms in meat at Mekelle city. METHODS: A descriptive survey design was used to answer questions concerning the current status of food hygiene and sanitation practiced in the abattoir and butcher shops. Workers from the abattoir and butcher shops were interviewed through a structured questionnaire to assess their food safety knowledge. Bacterial load was assessed by serial dilution method and the major bacterial pathogens were isolated by using standard procedures. RESULTS: 15.4% of the abattoir workers had no health certificate and there was no hot water, sterilizer and cooling facility in the abattoir. 11.3% of the butchers didn't use protective clothes. There was a food safety knowledge gap within the abattoir and butcher shop workers. The mean values of bacterial load of abattoir meat, butcher shops and street meat sale was found to be 1.1×10(5), 5.6×10(5) and 4.3×10(6) cfu/g, respectively. The major bacterial pathogens isolated were Escherichia coli, Staphylococcus aureus and Bacillus cereus. CONCLUSIONS: The study revealed that there is a reasonable gap on food safety knowledge by abattoir and butcher shop workers. The microbial profile was also higher compared to standards set by World Health Organization. Due attention should be given by the government to improve the food safety knowledge and the quality standard of meat sold in the city.